Agency and communion in A Day in the Life of a thriving older adult - Kubiliene, Neringa (Journal of religion, spirituality & aging, 2016)
A quasi-ecological case study of the agentive and communion strivings of a thriving older woman is reported here. Applying a resilience theoretical framework and employing a Day in the Life visual methodology, instances of agency and communion and their spiritual implications were explored in the filmed record of the woman's Day and in the transcriptions of interviews conducted both before and subsequent to filming. Examples of agency included practicing tai chi, inquisitiveness, and maintaining independence through overcoming obstacles posed by older age; examples of communion included reciprocal communication with community members, experiences of friendship and human connection, and care about others. The integration of both personal characteristics was interconnected both during the entire course of the Day and within the several examples described. Integration of agency and communion contributes to a generative pattern of functioning, and serves as a fundamental source of moral motivation, portraying a rich representation of this participant's thriving in ecological context.